Analisis Kelayakan dan Sensitivitas Usahatani Jagung di Dusun Sumuran Desa Ajung Kecamatan Ajung Kabupaten Jember - Haryanto, Wasis; Zuniana, Qory (KUBIS, 2024)
Corn "Zea mays L" is one of the world's most important food crops, apart from wheat and rice. The demand for corn is currently increasing, which can be seen in terms of production, where the demand for domestic and international markets is very high for food and feed needs. One of the corn-producing areas is in Sumuran hamlet, Ajung village. The aims of this research were 1) to find out how much the income of corn farming in Sumuran hamlet was, 2) to find out the level of feasibility of corn farming in Sumuran hamlet, 3) to find out the sensitivity of corn farming in Sumuran hamlet. The sampling method of this study used purposive sampling and the results of this study showed that the total revenue and costs in the corn farming income were IDR 54,756,688 and IDR 14,448,325. with the results of calculations using R/C with a result of 3.79 meaning that every IDR 1,000 of farming costs incurred generates revenue of IDR 3,790. and Net Present Value (NVP) with a 5% factor discount of IDR 36.782.011,46, with a 10% factor discount of IDR 33.539.756,6 and a 15% factor discount of IDR 30.752.693,005. And the value of the Internal Rate of Return (IRR) is 66,005% and the Payback Period (PP) is 0.11. So corn farming in Sumuran hamlet is feasible to try.